Antiviral therapy decreases GpIIb/IIIa activation of platelets in patients with chronic hepatitis C - Sieghart, Wolfgang; Homoncik, Monika; Jilma, Bernd; Formann, Elisabeth; Ferenci, Peter; Gangl, Alfred; Peck-Radosavljevic, Markus (Thrombosis and Haemostasis, 2006)
Interferon alpha (IFN-α) is used to treat haematological and solid malignancies and is the gold standard therapy for chronic hepatitisC infection in combination with ribavirin. It has a well known platelet lowering effect and was recently shown to impair platelet aggregation in the presence of various agonists and has been accused to increase patients’ bleeding risk during IFN-α therapy. Thus, we hypothesised that antiviral treatment decreases GpIIb/IIIa activation and affects global platelet function. In a prospective clinical trial, we examined the effects of combination therapy with pegylated IFN-α 2a (PegIFN-α 2a) and ribavirin on platelet GpIIb/IIIa activation and platelet secretion in 20 patients with chronic hepatitis C at week 2, 4, 8 and 12 after the beginning of therapy. In addition, we determined global platelet function (CEPI-CT) with the PFA-100 and vWF-Ag levels. Antiviral therapy significantly decreased GpIIb/IIIa activation in a time dependent manner, whereas markers of platelet secretion (P-selectin, β-thromboglobulin) remained unchanged. Despite a marked elevation of vWF-Ag levels, CEPI-CT did not change compared to baseline levels. Antiviral therapy significantly decreases GpIIb/IIIa activation in patients with chronic hepatitis C, while vWG-Antigen levels are markedly increased and α-granule secretion is not affected. This does not result in an alteration of global platelet function as assessed by the PFA-100, because elevated vWF-Antigen levels might compensate for the acquired defect.
Keywords: Platelet activation markers; von Willebrand factor; clinical / epidemiological studies